Denial of Family Violence in Court: An Empirical Analysis and Path Forward For Family Law - Meier, Joan S. (2021)
Scores of women and children have suffered grave harm from courts’ punitive responses to mothers’ requests to protect their children from paternal abuse in the context of custody litigation. Rather than responding protectively, family courts frequently turn on the protective parent, ordering the children removed from the protective parent and sending them to live with or spend unprotected time with their allegedly abusive parent. In the worst of these cases, the abusive parent has used this court-ordered access to murder the child(ren), in the ultimate act of revenge against his adult victim. While courts’ resistance to mothers’ and children’s abuse claims is widespread, it is especially intense when the alleged abuser turns the tables by accusing the mother and child of “parental alienation.” The author’s national empirical study of cases involving both abuse and alienation claims has now generated the first-ever objective data quantifying family courts’ systematic pattern of denying adult - and especially child – abuse. For instance, the study found that family courts only believed mothers’ child abuse allegations less than one-third of the time. They believed only 1 in 49 cases of child sexual abuse when the accused father crossclaimed that the mother was alienating. Approximately one-third of mothers alleging a father’s abuse lose custody; when the father crossclaims alienation, that increases to one-half.In response, this article urges a paradigm shift on domestic abuse for both family law practitioners and scholars. After describing myriad critiques of family court responses to domestic abuse from scholars and protective parents, it then validates these critiques with cutting-edge data from the author’s new study. Despite the robust critical literature, mainstream family law scholarship has ignored the issue while unintentionally reinforcing the obscuring and denying of domestic abuse in family courts. In short, while the #MeToo movement has lifted the veil that protected male sexual abusers of women in employment, this new recognition of men’s abuse of women in that setting has yet to penetrate either family courts or family law academia. The new, objective data provides a wake-up call.The pattern depicted by both the anecdotal reports and the data begs two critical questions: Why are family courts so resistant to allegations that a father is abusive, and how do courts implement this denial? Regarding “why,” the article offers both individual and structural answers, specifically (i) the individual psychology of denial and resistance to facing human atrocities, and (ii) family courts’ particular goals that fuel denial of men’s domestic abuse. Regarding “how,” the article – and the study – focus on the theory of parental alienation, which lacks scientific support but is nonetheless a key vehicle for family courts’ rejection of women’s abuse allegations.Finally, the article urges a shift among both scholars and professionals to reduce and constrain the minimization and denial of domestic abuse in custody matters. In academia, it challenges leading scholars to build their scholarship and teaching from a foundation that acknowledges the empirical realities of courts’ negative responses to abuse claims while challenging the common but misplaced confidence in courts’ adjudications. Regarding practice, it makes two concrete, specific and practical proposals for legislatures and courts. First, abuse allegations should be assessed upfront and separately, with parental alienation only considered if abuse is ruled out. Second, state law must legislate for indeterminacy, and avoid defaulting to falsity where the truth of an abuse allegation is uncertain. Courts must instead protect children from risk even when it is uncertain, while proceeding with caution to both maximize the potential for relationship repair and ensure child safety